PENGARUH CAPITAL ADEQUACY RATIO (CAR) DAN NET PROFIT MARGIN (NPM) TERHADAP RETURN ON ASSETS PT. BANK BRI SYARIAH TBK PERIODE 2015 – 2019 - Wida Lisnawati; Mulia Amirullah (Jurnal Ekonomi Rabbani, 2022)
The purpose of this research to knowing and analyze the influence of Capital Adequacy Ratio (CAR) and Net Profit Margin (NPM) to Return on Assets (ROA) of PT. Bank BRI Syariah Tbk for the period 2015 -2019. The method of this research used descriptive method and quantitative method. The data used is secondary data. To analyze data in this research used Multiple Linier Regresion and Determination Coefficients. Partially based on the result of this research Capital Adequacy Ratio (CAR) and Net Profit Margin (NPM) are significant effect to Return on Assets of PT. Bank BRI Syariah Tbk for the periode 2015 -2019 and simultaneously Capital Adequacy Ratio (CAR) and Net Profit Margin (NPM) are significant effect to Return on Assets of PT. Bank BRI Syariah Tbk for the periode 2015 -2019. PT. Bank BRI Syariah Tbk it is expected to further improve its performance in accelerating the growth rate of its profitability by means of absorption and optimaizing of funds, efficiency of capital and efficiency of costs.